THE ROLE OF THE EUROPEAN ANTI-FRAUD OFFICE (OLAF) IN THE REPORTEDCASES OF FRAUD ON THE FINANCIAL INTERESTS OF THE EUROPEAN UNION INREPUBLIC OF NORTH MACEDONIA (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2025)
As a candidate state for accession to the European Union, the Republic of North Macedonia, by signing the Framework Agreement on Financial Partnership between the European Commission and the Republic of North Macedonia, as a beneficiary of funds from the Instrument for Pre-accession Assistance (hereinafter referred to as 'IPA'), assumes the obligation to establish an efficient system for the protection of the financial interests of the European Union (hereinafter referred to as 'EU'), which will also contribute to the protection of the national financial interests of the state. The efficiency of the control system over the implementation of IPA funds is determined by various factors, as follows: the established controls within the national administrative bodies of the state administration and IPA structures; criminal-legal protection in cases of suspected fraud; the harmonization of national legislation with the legislation of the European Union; and the effective cooperation of national authorities with the established European institutions responsible in the respective area. This paper will provide a comprehensive assessment of the cooperation between national authorities and European institutions in the area of protection of EU financial interests, with special emphasis on the jurisdiction of the European Anti-Fraud Office (OLAF) as a sui generis institution of the European Union and the key institution responsible for investigating fraud, corruption, and other illegal activities that harm the financial interests of the EU. OLAF is an administrative body with specific investigative powers, and its structure and duties are detailed in EU regulations. In this regard, an overview of OLAF's regulation in terms of EU legislation will be elaborated, with special emphasis on the performance of OLAF’s duties in candidate states, particularly in cooperation with national law enforcement institutions, through a detailed normative analysis of relevant national and EU legislation. The paper will contribute to the process of enhancing the legal and institutional framework of the national system for the protection of EU financial interests, which will also have a direct impact on improving the protection of national financial interests.Keywords: OLAF, protection of the EU financial interests,law enfrocment institutions